Stiffening-Induced High Pulsatility Flow Activates Endothelial Inflammation via a TLR2/NF-κB Pathway - Tan, Yan (Public Library of Science, 2014)
Stiffening of large arteries is increasingly used as an independent predictor of risk and therapeutic outcome for small artery dysfunction in many diseases including pulmonary hypertension. The molecular mechanisms mediating downstream vascular cell responses to large artery stiffening remain unclear. We hypothesize that high pulsatility flow, induced by large artery stiffening, causes inflammatory responses in downstream pulmonary artery endothelial cells (PAECs) through toll-like receptor (TLR) pathways. To recapitulate the stiffening effect of large pulmonary arteries that occurs in pulmonary hypertension, ultrathin silicone tubes of variable mechanical stiffness were formulated and were placed in a flow circulatory system. These tubes modulated the simulated cardiac output into pulsatile flows with different pulsatility indices, 0.5 (normal) or 1.5 (high). PAECs placed downstream of the tubes were evaluated for their expression of proinflammatory molecules (ICAM-1, VCAM-1, E-selectin and MCP-1), TLR receptors and intracellular NF-κB following flow exposure. Results showed that compared to flow with normal pulsatility, high pulsatility flow induced proinflammatory responses in PAECs, enhanced TLR2 expression but not TLR4, and caused NF-κB activation. Pharmacologic (OxPAPC) and siRNA inhibition of TLR2 attenuated high pulsatility flow-induced pro-inflammatory responses and NF-κB activation in PAECs. We also observed that PAECs isolated from small pulmonary arteries of hypertensive animals exhibiting proximal vascular stiffening demonstrated a durable ex-vivo proinflammatory phenotype (increased TLR2, TLR4 and MCP-1 expression). Intralobar PAECs isolated from vessels of IPAH patients also showed increased TLR2. In conclusion, this study demonstrates for the first time that TLR2/NF-κB signaling mediates endothelial inflammation under high pulsatility flow caused by upstream stiffening, but the role of TLR4 in flow pulsatility-mediated endothelial mechanotransduction remains unclear.